Alternative polyadenylation regulation: insights from sequential polyadenylation. Issue 4 (20th October 2022) - Tang, Peng; Zhou, Yu
ABSTRACT: The processing of the proximal and distal poly(A) sites in alternative polyadenylation (APA) has long been thought to independently occur on pre-mRNAs during transcription. However, a recent study by our groups demonstrated that the proximal sites for many genes could be activated sequentially following the distal ones, suggesting a multi-cleavage-same-transcript mode beyond the canonical one-cleavage-per-transcript view. Here, we review the established mechanisms for APA regulation and then discuss the additional insights into APA regulation from the perspective of sequential polyadenylation, resulting in a unified leverage model for understanding the mechanisms of regulated APA.